IMPLEMENTATION OF MULTI-BLENDED LEARNING MODEL IN ENGLISH TEACHING AT THE REMOTE AREA SCHOOL IN BURU-MALUKU - Nirwana. AR; Mitha Rahmawati Pellu; Ibnu Hajar; Saidna Zulfiqar Bin Tahir (Universitas Muhammadiyah Makassar, 2023)
Multi-blended learning model was combination of four learning models. They were independent learning model, face to face learning model, small group learning model, and online learning model. This research employed descriptive qualitative method. The research sample consisted of one teacher and 36 students at SMA Negeri 2 Buru, Maluku. The collected data employed observation and interview, and then the data is presented descriptively. The result study was used to explain the challenges faced by teacher and students’ perception in implementation of Multi-Blended Learning Model in English teaching at the remote area school. The challenges faced in independent learning model were low interest and motivation to learn independently, low control and sufficient attention from parents, low support from parents, and low economic level of students’ parents. The second challenges faced in face to face classroom learning model were limited teaching time, large number of students in one class, and different English ability in one class. Several obstacles found in small group learning model were limited teaching time, and large number of students in one class. The obstacles found in online learning model was that some students did not have internet data package, so they could not update information and new materials optimally. Students’ perception that multi-blended learning model was very helpful for students to collaborate and interact among students and teacher. Students became enthusiastic to learn independently and understanding of teacher’s material well through video tutorial available on the teacher’s YouTube content.